The Correspondence Between Students’ and Teachers’ Views on Teachers’ Emotional Scaffolding Strategies in English Classes in Iran - Shahidzade, Farangis; Fazilatfar, Ali Mohammad; Razmi, Mohammad Hasan (Frontiers in Psychology, 2022)
Academic emotions can play a major role in students’ learning in their English classes. The literature about emotional scaffolding strategies is not widely developed; most of the studies merely focus on negative emotions in EFL contexts. However, in today's world of varied psychological elements, it is more critical than ever before to scaffold students’ positive emotions to provide more opportunities for their classroom engagement. This study is to explore teachers’ strategies of enhancing students’ positive emotions in English classes in Iran. To investigate the correspondence between students’ and teachers’ views on the effective emotional scaffolding strategies of English teachers, an exploratory sequential mixed-methods design was conducted. First, the researcher conducted semi-structured interviews with eleven high school students of Salami School in Kazeroun to collect in-depth qualitative data. Then, the interview-based Likert scale questionnaires were distributed and completed by sixty high school English teachers in Kazeroun for the quantitative data. According to the teachers’ self-reports, expressing optimism and hope about the students’ future lives and prospective jobs was the most frequently used strategy. There was a significant difference among the teachers' views on the emotional scaffolding strategies. Moreover, some of the strategies taken into consideration as effective strategies by the students are the least frequently used ones according to the teachers’ reports. The results and findings have several theoretical and practical implications for English teachers in EFL contexts; they might bolster their understanding of appropriate emotional scaffolding strategies preparing them to play a contributing role as great facilitators in English classes.